Implementation of a dual platelet inventory in a tertiary hospital during the COVID‐19 pandemic enabling cold‐stored apheresis platelets for treatment of actively bleeding patients. (22nd June 2022) - Braathen, Hanne; Hagen, Kristin G.; Kristoffersen, Einar K.; Strandenes, Geir; Apelseth, Torunn O.
Abstract: Background: To increase preparedness and mitigate the risk of platelet shortage without increasing the number of collections, we introduced a dual platelet inventory with cold‐stored platelets (CSP) with 14‐days shelf life for actively bleeding patients during the COVID‐19 pandemic. Study design and methods: We collected apheresis platelet concentrates with blood type O or A. All patients receiving CSP units were included in a quality registry. Efficacy was evaluated by total blood usage and laboratory analysis of platelet count, hemoglobin, and TEG 6s global hemostasis assay. Feasibility was evaluated by monitoring inventory and a survey among laboratory staff. Results: From 17 March, 2020, to 31 December, 2021, we produced 276 CSP units and transfused 186 units to 92 patients. Main indication for transfusion was surgical bleeding (88%). No transfusion reactions were reported. 24‐h post‐transfusion patient survival was 96%. Total outdate in the study period was 33%. The majority (75%) of survey respondents answered that they had received sufficient information and training before CSP was implemented. Lack of information about bleeding status while issuing platelets, high workload, and separate storage location was described as main reasons for outdates. Discussion: CSP with 14‐days shelf life is a feasible alternative for the treatment of patients with bleeding. Implementation of a dual platelet inventory requires thorough planning, including information and training of clinical and laboratory staff, continuous follow‐up of practice and patients, and an easy‐to‐follow algorithm for use of CSP units. A dual platelet inventory may mitigate the risk of platelet shortage during a pandemic situation.